3,3′-Bithiophene-Based Chiral Bisphosphine Oxides as Organocatalysts in Silicon-Derived Lewis Acid Mediated Reactions - Rossi, Sergio; Benincori, Tiziana; Raimondi, Laura Maria; Benaglia, Maurizio (Synlett, 2020)
This account summarizes the development of new biheteroaromatic chiral bisphosphine oxides. 3,3′-Bithiophene-based phosphine oxides (BITIOPOs) have been successfully used as organocatalysts to promote Lewis base catalyzed, Lewis acid mediated stereoselective transformations. These highly electron-rich compounds, in combination with trichorosilyl derivatives (allyltrichlorosilane and silicon tetrachloride), generate hypervalent silicon species that act as chiral Lewis acids in highly diastereo- and enantioselective organic reactions. Several relevant examples related to these applications are discussed in detail.1 Introduction2 The BITIOPO Family3 Enantioselective Opening of Epoxides4 Enantioselective Allylation of Aldehydes5 Stereoselective Direct (Double) Aldol-Type Reaction with Ketones6 Stereoselective Direct Aldol-Type Reaction with Ester Derivatives7 Conclusions
Keywords: silicon hypercoordination; organocatalysis; Lewis bases; aldol reactions; stereoselective reactions; chiral phosphine oxides